Analysis of Strengths, Weaknesses, Opportunities and Threats of the "Lesson Study" Course from the Perspective of Executives: A Mixed Methods Research - mahin naderi; Ebrahim Jafari; BIbi Eshrat Zamani; Mohammad Nikkhah (رویکردهای نوین آموزشی, 2020)
This study aimed to analyze the strengths, weaknesses, opportunities, and threats of the "lesson study" course from executives perspective. The study employed an exploratory sequential mixed methods research design. The sample size consisted of 20 subjects selected through a purposive chain sampling and data saturation in qualitative section. In the qualitative section, the sample was saturated through a semi-structured interview with 20 people. In the quantitative section, 294 teachers were selected as a sample using Cochran's formula. The data collection instrument was semi-structured in the qualitative part of the interview and a researcher-made questionnaire in the quantitative section.The validity of the questionnaire was confirmed by 5 professors of the curriculum and its reliability was obtained at 94% using Cronbach's alpha.  The data analysis instruments in the quantitative section was SPSS software v-23 and in the qualitative section was MAXQDA software. In the quantitative section descriptive and inferential statistical methods such as percentage, frequency, mean, and Friedman test were used. In the qualitative section, the semi-structured interviewing technique was employed. Findings of the qualitative research section were categorized into the most important strengths, weaknesses, opportunities and threats of the course, including components related to objectives, implementation and evaluation. The most important strengths are the participation promotion and exchange of views; the most critical weaknesses are its time-consuming nature, and restrictive laws are the most significant opportunities for developing culture and research capacity. The most critical threats were misunderstanding and lack of accountability in the lesson study course. The quantitative section results showed that development of participatory learning culture, theatrical performance of the lesson study course to participate in the festival, the publication of research resources on a large scale, and the course's time-consuming implementation are the most important strengths, weaknesses, opportunities, and threats of the lesson study course from the teachers' viewpoints.